2016
DOI: 10.1016/j.fertnstert.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic indicators of assisted reproduction technology outcomes of cycles with ultralow serum antimüllerian hormone: a multivariate analysis of over 5,000 autologous cycles from the Society for Assisted Reproductive Technology Clinic Outcome Reporting System database for 2012–2013

Abstract: Refusing treatment solely on the basis of ultralow AMH levels is not advisable, but patients should be counseled appropriately about the prognostic factors for cancellation and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 16 publications
1
19
0
3
Order By: Relevance
“…Reicheman et al [ 74 ] found 3.9 % clinical pregnancy rate in women with AMH <0.17 ng/ml and >42 years. Seifer et al [ 75 ] conducted the largest study in this area analyzing AMH concentrations in over 5000 cycles from the Society for Assisted Reproductive Technology Clinic Outcome Reporting System Database for 2012–2013. According to their data, the cycles of women with the AMH concentration lower than 0.16 ng/mL had a greatest risk of cancelation.…”
Section: Amh As An Indicator Of Fertility In Late Reproductive Age Womentioning
confidence: 99%
See 1 more Smart Citation
“…Reicheman et al [ 74 ] found 3.9 % clinical pregnancy rate in women with AMH <0.17 ng/ml and >42 years. Seifer et al [ 75 ] conducted the largest study in this area analyzing AMH concentrations in over 5000 cycles from the Society for Assisted Reproductive Technology Clinic Outcome Reporting System Database for 2012–2013. According to their data, the cycles of women with the AMH concentration lower than 0.16 ng/mL had a greatest risk of cancelation.…”
Section: Amh As An Indicator Of Fertility In Late Reproductive Age Womentioning
confidence: 99%
“…The different results in all above studies could be partially explained by different assays applied in different years [ 75 ]. In addition, even the similar kits achieved higher or lower values during the same time.…”
Section: Amh As An Indicator Of Fertility In Late Reproductive Age Womentioning
confidence: 99%
“…4 However, despite its strong correlation with ovarian response to stimulation in ART, AMH is a poor predictor of nonpregnancy with sensitivities between 19-66%, and specificities between 55-89% when using cut-offs ranging from <0.1-1.66 ng/mL (Table 1). 3 Notably, a recent study of the Society for Assisted Reproductive Technology database found that while women with ultralow AMH (<0.16 ng/ mL) had 54% cycle cancellation rate, the overall live birth rate per cycle start was 9.5%, 43 supporting the notion that denying infertility treatment solely on the basis of undetectable AMH is not advisable. Similarly, AMH is a poor predictor of pregnancy and live birth following ART, with 2 recent meta-analyses showing the AUC for AMH as predictor of clinical pregnancy and live birth to be 0.63 and 0.61, respectively.…”
Section: Early Follicular Follicle-stimulating Hormonementioning
confidence: 98%
“…D. Seifer и соавт. [23] провели самое крупное исследование в этой области, проанализировав концентрацию АМГ в более чем 5000 циклах из базы данных системы отчетов об итогах клинических исследований в области ВРТ за 2012-2013 гг. По их данным, пациентки с уровнем АМГ <0,16 нг/мл имели наибольший риск отмены цикла ЭКО.…”
unclassified
“…Важно отметить, что авторам не удалось установить определенный пороговый уровень АМГ, ниже которого беременность была бы исключена. Разница в результатах вышеприведенных исследований может быть частично объяснена применением различных методов оценки концентрации АМГ [23,28]. К сожалению, имеющиеся методы оценки не позволяют надежно предсказать исход лечения бесплодия у пациенток позднего репродуктивного возраста с низкими значениями АМГ, особенно у женщин старше 42 лет.…”
unclassified